Adjuvant Radiotherapy in Primary Adenoid Cystic Carcinoma of Trachea- A Case Series - Ahirwar, Manish Kumar; Nanda, Siddhartha; Mishra, Shiv Shankar; Parida, Sourajit (Asian Pacific Journal of Cancer Biology, 2022)
Objective: Only 1% of all malignancies of the respiratory system are adenoid cystic carcinoma (ACC) of the trachea. ACC’s clinical course is frequently lengthy. Most patients first experience dyspnea, which looks like asthma or chronic bronchitis. The primary treatment choice is surgical resection followed by radiotherapy due to the small surgical margins of the tumor. When surgery is not an option, most cancers respond to radiotherapy, which frequently produces prolonged periods of remission. Method: We present three cases of primary ACC of the trachea. One case involved a 49-year-old man who had tracheal ACC treated surgically and then with radiation. Another 65-year-old female patient underwent surgical resection and adjuvant radiotherapy to treat her recurrent metastatic posterior thoracic wall tumor. At one month follow-up, our patient showed no evidence of disease, and a 38-year-old male presented with complaints of dry cough, breathlessness, and hemoptysis. Bronchoscopy showed a polypoidal growth obstructing more than 2/3rd of the tracheal lumen. The patient underwent excision of the tracheal tumor followed by adjuvant radiotherapy. Conclusion: Postoperative adjuvant radiotherapy plays an important role in management of ACC and it should be considered in all the patients of ACC to decrease the risk of recurrent disease.